2015
DOI: 10.1016/j.seizure.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The perceived burden of epilepsy: Impact on the quality of life of children and adolescents and their families

Abstract: Epilepsy impairs all aspects of QoL, although at different degree, both in children/adolescents and in their families. Parental apprehensiveness appears to have a role on this, and it may not reflect the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 24 publications
1
43
4
5
Order By: Relevance
“…One means of enhancing the social support would be to provide PWE as well as their family members and caregivers with adequate epilepsy education. This would help reduce the stigma associated with the condition [45] while helping appreciate the legitimate needs of PWE [46]. The use of support groups for both caregivers and PWE also provide the much-needed emotional support through their interaction with other individuals and families in similar predicaments [47].…”
Section: Discussionmentioning
confidence: 99%
“…One means of enhancing the social support would be to provide PWE as well as their family members and caregivers with adequate epilepsy education. This would help reduce the stigma associated with the condition [45] while helping appreciate the legitimate needs of PWE [46]. The use of support groups for both caregivers and PWE also provide the much-needed emotional support through their interaction with other individuals and families in similar predicaments [47].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, social stigmas associated with epilepsy result in a sense of pessimism [8]. A study by Ellis demonstrated that stigma within the family is responsible for triggering some of the behavioral problems in PWEs [7].…”
Section: The Negative Effects On Families Caring For Patients With Epmentioning
confidence: 99%
“…Cianchetti et al [8] 2015 Utilized a questionnaire that assessed the quality of life (QoL) of adolescents with epilepsy and their family members. It concluded that epilepsy impairs all aspects of QoL.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to multiple cognitive, social, and behavioral sequelae, posttraumatic epilepsy (PTE) is a well‐described, long‐term complication of TBI, and one of the most common causes for acquired epilepsy in both the pediatric and adult population 3 . PTE may have severe consequences on the quality of life and neuropsychological functions of young patients 4,5 . Even if remission is achieved in adulthood, social and educational problems may persist.…”
Section: Introductionmentioning
confidence: 99%